The Median Nerve Injury Model in Pre-clinical Research – A Critical Review on Benefits and Limitations - Ronchi, Giulia; Morano, Michela; Fregnan, Federica; Pugliese, Pierfrancesco; Crosio, Alessandro; Tos, Pierluigi; Geuna, Stefano; Haastert-Talini, Kirsten; Gambarotta, Giovanna (Frontiers in Cellular Neuroscience, 2019)
The successful introduction of innovative treatment strategies into clinical practice strongly depends on the availability of effective experimental models and their reliable pre-clinical assessment. Considering pre-clinical research for peripheral nerve repair and reconstruction, the far most used nerve regeneration model in the last decades is the sciatic nerve injury and repair model. More recently, the use of the median nerve injury and repair model has gained increasing attention due to some significant advantages it provides compared to sciatic nerve injury. Outstanding advantages are the availability of reliable behavioural tests for assessing posttraumatic voluntary motor recovery and a much lower impact on the animal wellbeing. In this article, the potential application of the median nerve injury and repair model in pre-clinical research is reviewed. In addition, we provide a synthetic overview of a variety of methods that can be applied in this model for nerve regeneration assessment. This article is aimed at helping researchers in adequately adopting this in vivo model for pre-clinical evaluation of peripheral nerve reconstruction as well as for interpreting the results in a translational perspective.